High-gain wide-band dual-circular-polarised antenna design using dynamic constrained multi-objective evolutionary algorithm. (1st January 2014) - Liang, Xiaolei; Zeng, Sanyou
A high-gain wide-band dual-circular-polarised antenna is designed using a dynamic constrained multi-objective evolutionary algorithm (DCMOEA) in this paper. This antenna design is a constrained optimisation problem (COP). It has many constraints. Then we shall face two challenges to solve the problem. One is that it has huge local optima. The other is that feasible solutions are hard to find, or even no feasible solution exists in the problem. The DCMOEA in this paper has the potential capacity in solving such problem since multi-objective evolutionary algorithm can compromise conflict between global search and convergence rate. Then it is adopted to solve a COP after a COP is converted into an equivalent dynamic constrained multiobjective optimisation problem (DCMOP). The antenna design of NASAs TDRS-C communications satellite is employed to test this technique. A satisfactory antenna is found.